Early Cardiotoxic Remodelling Precedes Hepatic Fibrosis and Increases Susceptibility to Lethal Arrhythmias in Wild‐Type MASH Mice - Jinyao Liu; Kohmei Yamashita; Seiko Yamano (Clinical and Experimental Pharmacology and Physiology, 2026)
ABSTRACT Objective Metabolic dysfunction‐associated steatohepatitis (MASH) is increasingly linked to cardiovascular complications; however, the mechanisms underlying the association between hepatic injury and cardiotoxicity remain unclear. This study aimed to establish a wild‐type mouse model of MASH with cardiac involvement and to characterise the temporal relationship between hepatic and cardiac alterations during disease progression. Methods Male C57BL/6J mice were fed a standard diet or a low‐carbohydrate, high‐protein, high‐cholesterol (LCHP‐HC) diet with or without non‐excessive ethanol for 12 or 24 weeks. Arrhythmogenic susceptibility was assessed using provocation testing. Hepatic and cardiac alterations were evaluated by histology, immunofluorescence, and quantitative RT‐PCR. Results The LCHP‐HC diet combined with ethanol induced histological MASH and markedly increased susceptibility to lethal arrhythmias. At 12 weeks, cardiac remodelling characterised by inflammation, mild fibrosis, and connexin‐43 dysregulation was evident in the absence of hepatic fibrosis, indicating early cardiotoxic remodelling. At 24 weeks, hepatic fibrosis and hepatic sympathetic activation became evident, whereas local cardiac sympathetic activation remained unchanged, indicating a temporal dissociation in which cardiac remodelling preceded hepatic fibrotic progression. Conclusion Early cardiotoxic remodelling preceded hepatic fibrosis and was associated with increased arrhythmogenic susceptibility during MASH progression. These findings demonstrate that cardiac remodelling develops early in experimental MASH and reveal a stage‐dependent temporal association between hepatic disease progression and cardiac vulnerability.